Engineering of Thermovibrio ammonificans carbonic anhydrase mutants with increased thermostability. Issue 37 (April 2020) - Parra-Cruz, Ricardo; Lau, Phei Li; Loh, Hwei-San; Pordea, Anca
Highlights: Thermostable mutants of carbonic anhydrase from Thermovibrio ammonificans were prepared and characterized. Four mutants were identified with improved stability at 90 ᵒC, compared to the wild-type enzyme. Ultra-thermostable mutant N140 G exhibited a 3-fold increased time of half-life at 60 ᵒC. The most thermostable mutants showed a significantly enhanced esterase activity at high temperatures, up to 95 ᵒC. Abstract: Carbonic anhydrase can be used as an additive to improve the efficiency of carbon capture and utilisation processes, due to its ability to increase the rate of CO2 absorption into solvents. Successful industrial application requires robust carbonic anhydrases, able to withstand process conditions and to perform consistently over long periods of time. Tolerance of high temperatures, pH and salt concentrations are particularly desirable features. We have previously used molecular dynamics simulations to rationally design four mutants of Thermovibrio ammonificans carbonic anhydrase with increased rigidity, and we hypothesized that this will result in an increased thermostability. Herein, we report on the successful recombinant expression and characterization of these mutants. Four of the TaCA variants showed increased stability at 90 ᵒC during 1 h, compared to wild-type. Two out of the four mutations predicted by the theoretical studies resulted in marked stabilization of the protein, with up to 3-fold higher time of half-life for mutant N140 G compared to the wild-type enzyme at 60 ᵒC. A significantly 50-fold increased ester hydrolysis activity was also observed with the most thermostable variant at 95 ᵒC compared to 25 ᵒC, suggesting an increased flexibility of the active site at high temperatures.